Food Truck Customer’s Perception on Food Truck Service Provider’s Service Quality: Customer Confidence as Mediator - Kumar, Kavigtha Mohan (Journal of Entrepreneurship, Business and Economics, 2024)
The food truck industry has gained a lot of prominence in Malaysia due to its effective mode of starting in terms of cost and risks involved. It has stood a chance to compete fairly with restaurants and other structures set to sell fast food and beverages. It is due to its emergency that a lot of studies have been conducted to determine its efficiency and quality of products sold by these food truck providers. This has led to some sort of neglect on the perception customers have on the quality of service offered by food truck provides. This study is thus an exploration of perception the customers have on quality of services provided by trucks and how this influences their repurchase intention and intention to recommend to food truck providers. Key concepts of this research have been divided into three variables and SOR model were used. The item for independent variable consist of assurance, tangibility, empathy, reliability and responsiveness, and customer recovery ; dependent variable consist of repurchase intention and intention to recommend, and the mediating variable of customer confidence were helps to develop the research hypotheses with the general aim being investigating what customers call quality services and how this boosts their confidence leading to repurchase intentions and intention to recommend to food truck providers. To achieve the results for this study, and effective results for that matter, this research employs a quantitative form of study. By interacting with a sample of willing 241 respondents this study is hoped to promote and provide data that can be relied upon and as well be used for establishing gaps existed in research on food truck service providers. It has been found from this research that assurance and customer recovery have direct and indirect effect on customer confidence and repurchase intention and intention to recommend. Meanwhile, tangibility, empathy and reliability and responsiveness have no direct and indirect effect. Furthermore, customer confidence plays a positive impact on both independent variable. These items used and results gained from this study is on service quality and food truck is new in the research field and these results could be the starting point of future researches. Research paper Keywords: Food Trucks; Revisit Intentions; Assurance; Tangibility; Empathy; Reliability and Responsiveness; Customer Confidence; Customer Recovery Reference to this paper should be made as follows: Kumar, K. M. (2023). Food Truck Customer’s Perception on Food Truck Service Provider’s Service Quality: Customer Confidence as Mediator. Journal of Entrepreneurship, Business and Economics , 11 (2), 201–244.